2020
DOI: 10.3390/ijms21124502
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Brain-Specific Treatment Effects in NPC1 Disease by Focusing on Cellular and Molecular Changes of Sphingosine-1-Phosphate Metabolism

Abstract: Niemann–Pick type C1 (NPC1) is a lysosomal storage disorder, inherited as an autosomal-recessive trait. Mutations in the Npc1 gene result in malfunction of the NPC1 protein, leading to an accumulation of unesterified cholesterol and glycosphingolipids. Beside visceral symptoms like hepatosplenomegaly, severe neurological symptoms such as ataxia occur. Here, we analyzed the sphingosine-1-phosphate (S1P)/S1P receptor (S1PR) axis in different brain regions of Npc1−/− mice and evaluated specific effects of treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 92 publications
(135 reference statements)
0
11
0
Order By: Relevance
“…Importantly, in both male and female wild type mice, COMBI treatment caused a significant reduction in brain weight. Our hypothesis that COMBI treatment in wild type mice results in concentrations of cholesterol and other lipids below or above normal levels, interfering with normal cellular or membrane functions, was substantiated by Gläser et al [ 103 ]. They showed that COMBI treatment of NPC1 +/+ mice resulted in strongly decreased S1P amounts in all brain regions investigated [ 103 ].…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Importantly, in both male and female wild type mice, COMBI treatment caused a significant reduction in brain weight. Our hypothesis that COMBI treatment in wild type mice results in concentrations of cholesterol and other lipids below or above normal levels, interfering with normal cellular or membrane functions, was substantiated by Gläser et al [ 103 ]. They showed that COMBI treatment of NPC1 +/+ mice resulted in strongly decreased S1P amounts in all brain regions investigated [ 103 ].…”
Section: Discussionmentioning
confidence: 71%
“…Seemingly, HPßCD could positively change yet unknown parameters that positively influence brain development. Nevertheless, after COMBI treatment, lipid analyses in various regions of NPC1 −/− mice showed disrupted sphingosine-1-phosphate lipid (S1P) metabolism in all brain regions, together with distinct changes in S1pr3/S1PR3 expression [ 103 ]. Interestingly, brain regions of NPC1 −/− mice showed only weak COMBI-treatment effects in these parameters [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the case of the lipid chelators 2-hydroxypropyl-β-cyclodextrin (HPBCD) and 2-hydroxypropyl-γ-cyclodextrin (HPGCD), which favor the degradation/exocytosis of macromolecules through the generation of inclusion complexes with cholesterol, sphingomyelin, lipids and GM2 gangliosides in in vitro models of NPC ( Soga et al, 2015 ), Niemann–Pick disease type A (NPA) ( Long et al, 2016 ), Neuronal Ceroid Lipofucinosis (NCL) ( Sima et al, 2018 ) and Tay-Sachs disease (TSD) ( Vu et al, 2018 ). Studies on hiPSC-derived NPC neural cultures showed a dose-dependent neurotoxic effects of HPBCD ( Long et al, 2016 ), which is currently used to treat NPC patients ( Matsuo et al, 2013 ; Ory et al, 2017 ; Hastings et al, 2019 ; Ulloa et al, 2020 ), thus anticipating recent in vivo studies showing a region-specific alteration of the homeostasis of different lipid species in the brain of HPBCD-treated mice with potential detrimental effects that should to be carefully evaluated ( Long et al, 2016 ; Glaser et al, 2020 ).…”
Section: Hipsc-derived Nscs To Develop New Therapeutic Strategiesmentioning
confidence: 99%